Omics Analysis of Blood-Responsive Regulon in Bordetella pertussis Identifies a Novel Essential T3SS Substrate - Drzmisek, Jakub; Stipl, Daniel; Petrackova, Denisa; Vecerek, Branislav; Dienstbier, Ana (International journal of molecular sciences, 2021)
Bacterial pathogens sense specific cues associated with different host niches and integrate these signals to appropriately adjust the global gene expression. Bordetella pertussis is a Gram-negative, strictly human pathogen of the respiratory tract and the etiological agent of whooping cough (pertussis). Though B. pertussis does not cause invasive infections, previous results indicated that this reemerging pathogen responds to blood exposure. Here, omics RNA-seq and LC-MS/MS techniques were applied to determine the blood-responsive regulon of B. pertussis. These analyses revealed that direct contact with blood rewired global gene expression profiles in B. pertussis as the expression of almost 20% of all genes was significantly modulated. However, upon loss of contact with blood, the majority of blood-specific effects vanished, with the exception of several genes encoding the T3SS-secreted substrates. For the first time, the T3SS regulator BtrA was identified in culture supernatants of B. pertussis. Furthermore, proteomic analysis identified BP2259 protein as a novel secreted T3SS substrate, which is required for T3SS functionality. Collectively, presented data indicate that contact with blood represents an important cue for B. pertussis cells.
Keywords: transkriptom; Chromatography, Liquid; omics analyses; Virulence Factors; Bacterial Proteins; gene expression; virulence; anotace sekvence; výpočetní biologie; tandemová hmotnostní spektrometrie; Transcriptome; Genomics; regulace genové exprese u bakterií; stanovení celkové genové exprese; Virulence; chromatografie kapalinová; faktory virulence; Gene Expression Profiling; proteomika; Bordetella pertussis; blood exposure; lidé; Type III Secretion Systems; Humans; T3SS; protein secretion; bakteriální proteiny; Molecular Sequence Annotation; sekreční systém typu III; Proteomics; Tandem Mass Spectrometry; Computational Biology; Gene Expression Regulation, Bacterial; genomika